THU0216 Serum cxcl16 levels in rf+/acpa+rheumatoid arthritis patients before and after treatment with dmards. (12th June 2018) - Ramamoorthy, R.; Tamilselvam, T.N.; Kumar, B.
Abstract : Background: Rheumatoid arthritis (RA) is characterised by profound mononuclear cell (MNC) recruitment into synovial tissue (ST). Studies have shown that chemokine CXCL16 is a premier MNC recruiter in RA. CXCL16 contributes to chronic inflammation, since it is highly expressed in RA synovial fluid (SF), is a potent chemoattractant for mononuclear cells (MNCs) in vitro, and is chemotactic for peripheral blood mononuclear cells (PBMCs) to RA ST in vivo . Hence treatment for RA will reflect change in serum CXCL16 levels Objectives: The aim of this study was to analyse the change of serum chemokine level of CXCL16, in patients with either RF +or ACPA +rheumatoid arthritis (RA), by DMARDs treatment. Methods: This was a prospective interventional study done in a tertiary care centre. 31 patients with RA were recruited for a period of 12 months. Serum CXCL16 levels were assayed in them along with other baseline investigations. The patients were treated with DMARDs. CXCL16 levels post treatment were measured after 6 months. For comparison another group of age and sex matched controls was taken (n=18) and their serum CXCL16 was also recorded. The serum CXCL16 levels were correlated with disease activity. Results: After treatment with conventional DMARDs 26 patients showed lowering of mean serum CXCL16 levels from 56.07 pg/ml to 21.79 pg/ml (62% reduction) after 6 months. The patients who showed inadequate response to conventional DMARD treatment (n=5) underwent therapy with biological DMARDs(TNF-α blocker) which reduced their CXCL16 levels from 63.81 pg/ml to 12.36 pg/ml (80.6% reduction) in subsequent 6 months. There was a corresponding improvement in the disease activity of RA. Lowering of CXCL16 was found to correlate positively with improvement of symptoms and lowering of disease activity Conclusions: DMARDs treatment significantly lowered the serum levels of CXCL16 in patients with RA. CXCL16 is one of the crucial chemokines regulated by DMARDs treatment Reference: [1] Ruth JH, Haas CS, Park CC, et al. CXCL16 Mediated cell recruitment to Rheumatoid Arthritis Synovial Tissue and Murine Lymph Nodes is dependent upon the MAPK pathway. Arthritis and Rheumatism2006;765–778. doi:10.1002/art.21662 Disclosure of Interest: None declared